Associations between human exposure to polybrominated diphenyl ether flame retardants via diet and indoor dust, and internal dose: A systematic review. (July 2016) - Bramwell, Lindsay; Glinianaia, Svetlana V.; Rankin, Judith; Rose, Martin; Fernandes, Alwyn; Harrad, Stuart; Pless-Mulolli, Tanja
Abstract: The aim of this review was to identify and appraise the current international evidence of associations between concentrations of polybrominated diphenyl ethers (PBDEs) in humans and their indoor dusts and food. We systematically searched Medline, Embase, Web of Science and Scopus (up to Jan 2015), using a comprehensive list of keywords, for English-language studies published in peer-reviewed journals. We extracted information on study design, quality, participants, sample collection methods, adjustments for potential confounders and correlations between PBDE concentrations in internal and external matrices. Of 131 potential articles, 17 studies met the inclusion criteria and were included in the narrative synthesis. We concluded that three key factors influenced correlations between external and internal PBDE exposure; half-life of individual congeners in the human body; proximity and interaction between PBDE source and study subject; and time of study relative to phase out of PBDE technical products. Internal dose of Penta-BDE technical mix congeners generally correlated strongly with dust. The exception was BDE-153 which is known to have higher persistence in human tissues. Despite the low bioaccessibility and short half-life of BDE-209, its high loading in dusts gave strong correlations with body burden where measured. Correlations between PBDE concentrations in duplicate diet and body burden were not apparent from the included studies. Whether dust or diet is the primary exposure source for an individual is tied to the loading of PBDE in dust or food items and the amounts ingested. Simple recommendations such as more frequent hand washing may reduce PBDE body burden. Highlights: Differing regional regulatory requirements have created distinct congener patterns. Dust or diet can be the primary PBDE exposure source dependant on global region. Duration since PBDE product ban and congener t1/2 influence internal dose patterns Proximity and interaction with items containing PBDE influence individuals' exposures. BDE-153 shows the highest persistence in human tissues.